Tailoring Social Protection to Small Island Developing States : Lessons Learned from the Caribbean - Williams, Asha; Cheston, Timothy; Coudouel, Aline; Subran, Ludovic (World Bank, Washington, DC, 2013)
This paper examines the role of social protection (SP) in Small Island Developing States (SIDS), given their particular structural, human resource and capacity constraints. While it focuses on SIDS in Latin America and the Caribbean, the lessons may be relevant to other SIDS with similar challenges. Caribbean SIDS have made significant commitment to address the needs of the vulnerable, as reflected by their level of SP spending, and the numerous safety net programs, labor market interventions, and insurance schemes. Nevertheless gaps remain, as many vulnerable groups are underserved and the systems show limited responsiveness to shocks. This is further hampered by duplication of efforts which limits the efficiency of interventions. The paper recommends a series of systemic efforts to: 1) harmonize SP systems and policies across the region to better respond to increased regional mobility; 2) consolidate SP programs within countries to improve efficiency; 3) foster key human capital improvements among the poor to break inter-generational transmission of poverty; 4) improve monitoring and evaluation systems and data collection capacity to facilitate more responsive SP programs; and 5) increase partnerships with civil society and private sector. At the thematic level, the paper recommends: a) improving the responsiveness to economic and environmental shocks; b) improving efficiency and effectiveness of social safety net programs, in particular cash transfer programs; c) tailoring labor market interventions to respond to constraints faced in the SIDS context; and d) reforming social insurance schemes, particularly pension schemes, to address current deficiencies and ensure readiness to respond to impending ageing.